A role for cohesin in T-cell-receptor rearrangement and thymocyte differentiation - Seitan, VC; Hao, B; Tachibana-Konwalski, K; Lavagnolli, T; Mira-Bontenbal, H; Brown, K; Teng, G; Carroll, T; Terry, A; Horan, K; Marks, H; Adams, D; et al. (2011)
Cohesin enables post-replicative DNA repair and chromosome segregation by holding sister chromatids together from the time of DNA replication in S phase until mitosis. There is growing evidence that cohesin also forms long-range chromosomal cis-interactions and may regulate gene expression in association with CTCF, mediator or tissue-specific transcription factors. Human cohesinopathies such as Cornelia de Lange syndrome are thought to result from impaired non-canonical cohesin functions, but a clear distinction between the cell-division-related and cell-division-independent functions of cohesion-as exemplified in Drosophila-has not been demonstrated in vertebrate systems. To address this, here we deleted the cohesin locus Rad21 in mouse thymocytes at a time in development when these cells stop cycling and rearrange their T-cell receptor (TCR) Î ± locus (Tcra). Rad21-deficient thymocytes had a normal lifespan and retained the ability to differentiate, albeit with reduced efficiency. Loss of Rad21 led to defective chromatin architecture at the Tcra locus, where cohesion-binding sites flank the TEA promoter and the EÎ ± enhancer, and demarcate Tcra from interspersed Tcrd elements and neighbouring housekeeping genes. Cohesin was required for long-range promoter-enhancer interactions, Tcra transcription, H3K4me3 histone modifications that recruit the recombination machinery and Tcra rearrangement. Provision of pre-rearranged TCR transgenes largely rescued thymocyte differentiation, demonstrating that among thousands of potential target genes across the genome, defective Tcra rearrangement was limiting for the differentiation of cohesin-deficient thymocytes. These findings firmly establish a cell-division-independent role for cohesin in Tcra locus rearrangement and provide a comprehensive account of the mechanisms by which cohesin enables cellular differentiation in a well-characterized mammalian system. © 2011 Macmillan Publishers Limited. All Rights Reserved.